The Powers and Perils of Solitude: Perspectives from Eighteenth-Century French Literature, Religion, and Medicine - Vila, Anne (Ruch Filozoficzny, 2024)
This article examines various meanings of solitude in eighteenth-century Europe, with emphasis on French thought and culture. Part 1 is a survey of literary representations of solitude and contemplation. Part II is devoted to the Jansenist convulsionnaires, Catholic dissidents who took part in a larger appeal against the repressive Unigenitus Bull of 1713. Although the convulsionary movement sought to attract crowds and publicity, it was also grounded in a Jansenist tradition of spiritual retreat that was emulated by the movement’s de facto patron saint, the appellant deacon François de Pâris. Part III features writings by Zimmermann and Tissot, who medicalized solitude for three reasons: belief in the ethos of sociability, concern over the pathogenic powers of the imagination, and suspicion towards the passions that drove some people to fix their minds exclusively on certain ideas. To show solitude’s harmful consequences for those who spent too much time absorbed in ideas, they made intriguing connections between secular knowledge-seekers and the religiously devout. The Jansenist convulsionnaires were one of the dangerously zealous groups whom they cited to illustrate their arguments.